Clean environment-friendly charcoal

By using functional binders with modified starch and pentaerythritol allyl ether, combined with the method of replacing anthracene coal by orchid, the problem of poor anti-broken performance and insufficient combustion of gasified carbon is solved, and efficient, environmentally friendly clean and environmentally friendly carbon preparation is achieved, which significantly reduces pollutant emissions.

CN119899709AInactive Publication Date: 2025-04-29XINJIANG LONGLIZE ENVIRONMENTALLY FRIENDLY CLEAN COAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510183845.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-19
Publication Date
2025-04-29
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the starch-based adhesives for preparing gasified carbon have poor crushing resistance, insufficient combustion, and difficult to meet environmentally friendly emission standards.

Method used

Modified starch is used as a functional binder, and the bonding strength and combustion performance are improved by combining with components such as pentaerythritol allyl ether and initiator, and the replacement of traditional anthracite by orchid is improved to improve environmental protection performance.

Benefits of technology

It significantly improves the anti-broken and combustion performance of clean and environmentally friendly carbon, reduces the ash and sulfur content, meets the standards of clean gasified carbon, and uses orchid carbon replacement, significantly reduces the emission of PM2.5, carcinogens and haze-causing substances.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of fuel, and particularly discloses clean environment-friendly charcoal which is prepared by the following steps: S1, preparing the following raw materials in parts by weight: 100-110 parts of semi-coke powder, 15-17 parts of deionized water and 9-12 parts of a functional adhesive; s2, preparing clean environment-friendly charcoal; the modified starch is added, the modified starch contains a flexible long-chain alkane structure, a calcium gluconate structure and unsaturated double bonds, the flexible long-chain alkane structure can be entangled with a flexible alkyl chain in pentaerythritol allyl ether, and the calcium gluconate structure not only contains inflammable carbon, oxygen and hydrogen elements, but also contains unsaturated double bonds. Calcium ions can play roles in fixing sulfur and promoting combustion, unsaturated double bonds can be chemically crosslinked under the action of an initiator, and through the synergistic effect of the calcium ions and the unsaturated double bonds, the crushing resistance of the gasified carbon is improved, the combustion is promoted, and the pollution is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of fuel technology, and more specifically, to clean and environmentally friendly carbon. Background Art

[0002] The particle size of semi-coke is generally greater than 3mm. It has the characteristics of high fixed carbon, high specific resistivity, high chemical activity, high specific surface area, good thermal stability, low ash, low sulfur, low aluminum, and low phosphorus. It is a good clean fuel. However, semi-coke has poor compressive strength and crushing resistance. During transportation and use, semi-coke powder that cannot be used directly will be produced, which greatly reduces the performance of semi-coke. In recent years, with the rise in the price of smokeless pulverized coal with good activity, the waste semi-coke powder and adhesives such as starch glue are bonded together to form gasified coal, which can not only reduce costs but also turn waste into treasure.

[0003] However, in the prior art, the starch-based adhesive used to prepare gasified coal has the problem of low bonding strength, which can easily lead to damage of the prepared gasified charcoal during use and transportation. At the same time, the addition of starch-based adhesives makes the prepared environmentally friendly charcoal prone to incomplete combustion and produces a large amount of nitrogen oxides, making it difficult to meet environmentally friendly emission standards. Based on the above statements, the present application provides clean and environmentally friendly charcoal. Summary of the invention

[0004] In order to solve the problems of poor anti-breakage performance and incomplete combustion during use of starch-based adhesives used to prepare gasified carbon, which fail to meet environmental emission standards, the present application provides clean and environmentally friendly carbon.

[0005] The present application provides clean and environmentally friendly carbon, which is prepared by the following steps: Step S1, preparing the following raw materials in parts by weight: 100-110 parts of blue charcoal coke powder, 15-17 parts of deionized water and 9-12 parts of functionalized binder; Step S2, preparing clean and environmentally friendly carbon: mixing the blue carbon powder and the functionalized binder evenly, adding deionized water, and then pressing them into 3-8 cm long strips or balls, and drying them to obtain clean and environmentally friendly carbon.

[0006] Preferably, during the compression molding process, the pressure is 6-10 MPa.

[0007] Preferably, the functionalized adhesive is prepared by the following steps: Step A1, prepare the following raw materials in parts by weight: 16-32 parts of corn starch, 12-24 parts of deionized water, 18-36 parts of sodium tripolyphosphate, 22-40 parts of modified starch, 6-10 parts of pentaerythritol allyl ether and 0.3-0.5 parts of initiator solution; Step A2, gelatinization: add corn starch and sodium tripolyphosphate to 1 / 3 weight part of deionized water, raise the temperature to 65-75° C. while stirring, and continue stirring for 10-20 minutes to obtain gelatinized corn starch; Step A3, free radical polymerization: add the modified starch to the remaining weight of deionized water, stir evenly, add the gelatinized corn starch prepared in step S2 while stirring, continue stirring for 2-3 hours, then add pentaerythritol allyl ether and initiator solution, heat to 76-80°C, continue stirring for 6-8 hours to obtain a functionalized adhesive.

[0008] Preferably, the initiator solution is an ammonium persulfate solution with a mass fraction of 10%.

[0009] Preferably, the blue charcoal coke powder is prepared by the following steps: The semi-coke is crushed and sieved into two particle sizes of 0-1mm and 1-3mm, and mixed evenly at a ratio of 4-5:1 to obtain semi-coke coke powder.

[0010] Preferably, the modified starch is prepared by the following steps: Step B1, corn starch and deionized water are mixed at 35-45°C, the pH value is adjusted to 8.5-9.5, and then a mixed solution a of octenyl succinic anhydride and isopropanol is added dropwise, and the dripping is controlled to be completed within 30 minutes. After the dripping is completed, the temperature is raised to 65-75°C, and the stirring reaction is continued for 4-6 hours. After the reaction is completed, the pH value is adjusted to 5.5-6.5, washed to neutral, dried, crushed, and passed through a 40-60 mesh sieve to obtain esterified corn starch, wherein corn starch, deionized water and mixed solution a are added dropwise to obtain esterified corn starch. The mass ratio of the mixed liquid a is 1-3:25-35:110, and the mass ratio of octenyl succinic anhydride to isopropanol in the mixed liquid a is 2-4:110. In the above reaction process, deionized water is used as a solvent and sodium hydroxide solution is used as an alkali catalyst. Corn starch and octenyl succinic anhydride undergo a ring-opening esterification reaction to obtain esterified corn starch. The amount of octenyl succinic anhydride is controlled to be slightly higher than that of corn starch, so that during the reaction, there are still remaining carboxyl groups to participate in the subsequent reaction process; Step B2, adding esterified corn starch to anhydrous DMF, stirring evenly, adding tetrabutylammonium bromide, epoxy compound and anhydrous DMF mixed solution b dropwise while stirring, and controlling the dropping to be completed within 30 minutes. After the dropping is completed, the temperature is raised to 70-80°C, and the reaction is stirred for 4-6 hours. After the reaction is completed, centrifugation, washing, and drying are performed to obtain modified starch, wherein the mass ratio of esterified corn starch, anhydrous DMF and mixed solution b is 2-4:60-80:15-25, and the mass ratio of tetrabutylammonium bromide, epoxy compound and anhydrous DMF in the mixed solution b is 0.04-0.06:0.3-0.6:20-30. In the above reaction process, anhydrous DMF is used as solvent, and the carboxyl group on the esterified corn starch undergoes a ring-opening reaction with the epoxy group on the epoxy compound to obtain the modified starch.

[0011] Preferably, the epoxy compound is prepared by the following steps: Calcium gluconate and triethylamine are added to anhydrous DMF, mixed evenly under an ice-water bath, and then a mixed solution c of epichlorohydrin and anhydrous DMF is added dropwise, and the dripping is controlled to be completed within 15 minutes. The temperature is raised to 55-65°C, and the reaction is stirred for 8-10 hours. After the reaction is completed, the reaction is filtered, and the filtrate is rotary evaporated. The rotary evaporated product is placed in acetone and dissolved, filtered, and the filtrate is rotary evaporated to constant weight to obtain an epoxy compound, wherein the mass ratio of calcium gluconate, triethylamine, anhydrous DMF, mixed solution c and acetone is 2-4: 0.1-0.3: 40-50: 15-25: 30-40, and the mass ratio of epichlorohydrin and anhydrous DMF in the mixed solution c is 0.4-0.8: 12-16. In the above reaction process, the active hydroxyl group on the calcium gluconate and the chlorine atom on the epichlorohydrin undergo nucleophilic substitution reaction to obtain the epoxy compound.

[0012] In summary, this application has the following beneficial effects: (1) In order to improve the anti-crushing performance and combustion performance of the clean and environmentally friendly carbon, the present invention adds modified starch, which contains a flexible long-chain alkane structure, a calcium gluconate structure and an unsaturated double bond. The presence of the flexible long-chain alkane structure can entangle with the flexible alkyl chain in pentaerythritol allyl ether, thereby improving the bonding strength of the starch adhesive and further improving the anti-crushing performance of the clean and environmentally friendly carbon. The presence of the calcium gluconate structure, on the one hand, contains a large amount of carbon, oxygen and hydrogen elements in its molecular chain, which can promote the full combustion of the starch-based adhesive. On the other hand, the calcium ions not only It has good water solubility, reduces the ignition point of the adhesive, can promote the full combustion of starch-based adhesives, and can also react with sulfur dioxide to play a role in sulfur fixation. In addition, calcium ions can react with sodium tripolyphosphate to further improve the anti-breakage performance of clean and environmentally friendly carbon. The presence of unsaturated double bonds can react with the unsaturated double bonds on pentaerythritol allyl ether under the action of initiators to undergo free radical polymerization reactions, introducing a large amount of carbon, oxygen and hydrogen elements, which not only further enhances the anti-breakage performance of clean and environmentally friendly carbon, but also promotes the full combustion of clean and environmentally friendly carbon.

[0013] (2) Compared with traditional anthracite, the use of lignite in this application to replace traditional anthracite is more environmentally friendly, with a 93% reduction in PM2.5, a 92% reduction in carcinogens, a 98% reduction in haze-causing substances, and a 97% reduction in polycyclic aromatic hydrocarbons. DETAILED DESCRIPTION

[0014] In order to make the implementation methods of the present application easier to understand, the present application will be described in detail below in conjunction with specific examples. These examples are only for illustration and are not limited to the scope of application of the present application.

[0015] The corn starch was Hengye brand industrial grade waxy corn starch produced by Hubei Xinghengye Technology Co., Ltd.; The contents of the blue carbon raw powder and its components used in Examples 1-6 and Comparative Examples 1-6 are as follows: Table 1 Main chemical composition of raw materials used in this application %

[0016] The present application is further described in detail below with reference to the embodiments.

[0017] Preparation Examples 1-3 and Comparative Preparation Example 1 provide methods for preparing epoxy compounds.

[0018] Preparation Example 1 Epoxy compounds are prepared by the following steps: Calcium gluconate and triethylamine were added to anhydrous DMF, and stirred at a speed of 400 rpm for 30 min under an ice-water bath until uniform. Then, a mixed solution c of epichlorohydrin and anhydrous DMF was added dropwise, and the dropping was completed within 15 min. The temperature was raised to 55°C, and the reaction was stirred for 10 h. After the reaction was completed, the mixture was filtered, and the DMF was removed by rotary evaporation of the filtrate. The rotary evaporation product was dissolved in acetone, and then the triethylamine hydrochloride was removed by filtration. The filtrate was rotary evaporated to remove acetone to obtain an epoxy compound, wherein the mass ratio of calcium gluconate, triethylamine, anhydrous DMF and the mixed solution c to acetone was 2:0.1:40:15:30, and the mass ratio of epichlorohydrin and anhydrous DMF in the mixed solution c was 0.4:12.

[0019] Preparation Example 2 The epoxy compound package is prepared by the following steps: Calcium gluconate and triethylamine were added to anhydrous DMF, and stirred at a speed of 500 rpm for 20 minutes under an ice-water bath until uniform. Then, a mixed solution c of epichlorohydrin and anhydrous DMF was added dropwise, and the dropping was completed within 15 minutes. The temperature was raised to 60°C, and the reaction was stirred for 9 hours. After the reaction was completed, the solution was filtered, and the DMF was removed by rotary evaporation of the filtrate. The rotary evaporation product was dissolved in acetone, and then the triethylamine hydrochloride was removed by filtration. The filtrate was rotary evaporated to remove acetone to obtain an epoxy compound, wherein the mass ratio of calcium gluconate, triethylamine, anhydrous DMF, mixed solution c and acetone was 3:0.2:45:20:30, and the mass ratio of epichlorohydrin and anhydrous DMF in the mixed solution c was 0.6:14.

[0020] Preparation Example 3 Epoxy compounds are prepared by the following steps: Calcium gluconate and triethylamine were added to anhydrous DMF, and stirred at a speed of 600 rpm for 10 min under an ice-water bath until uniform. Then, a mixed solution c of epichlorohydrin and anhydrous DMF was added dropwise, and the dropping was completed within 15 min. The temperature was raised to 65°C, and the reaction was stirred for 8 h. After the reaction was completed, the reaction was filtered, and the anhydrous DMF was removed by rotary evaporation of the filtrate. The rotary evaporation product was dissolved in acetone, and then the triethylamine hydrochloride was removed by filtration. The filtrate was rotary evaporated to remove acetone to obtain an epoxy compound, wherein the mass ratio of calcium gluconate, triethylamine, anhydrous DMF, mixed solution c and acetone was 4:0.3:50:25:40, and the mass ratio of epichlorohydrin and anhydrous DMF in the mixed solution c was 0.8:16.

[0021] Comparative Preparation Example 1 Epoxy compounds are prepared by the following steps: Add glucose and triethylamine to anhydrous DMF, stir at a speed of 400 rpm for 30 minutes under an ice-water bath until uniform, then add dropwise a mixed solution c of epichlorohydrin and anhydrous DMF, control the dripping to be completed within 15 minutes, raise the temperature to 55°C, stir and react for 10 hours. After the reaction is completed, filter, and evaporate the filtrate to remove DMF. Dissolve the rotary evaporated product in acetone, filter to remove triethylamine hydrochloride, and evaporate the filtrate to remove acetone to obtain an epoxy compound, wherein the mass ratio of glucose, triethylamine, anhydrous DMF, mixed solution c and acetone is 2:0.1:40:15:30, and the mass ratio of epichlorohydrin and anhydrous DMF in the mixed solution c is 0.4:12.

[0022] Preparation Examples 4-6 and Comparative Preparation Examples 2-3 provide methods for preparing modified starch.

[0023] Preparation Example 4 Modified starch is prepared by the following steps: Step B1, corn starch and deionized water are stirred at 35° C. and the speed is controlled to be 500 rpm for 30 min until uniform, the pH value is adjusted to 8.5 with 0.6M sodium hydroxide aqueous solution, and then a mixed solution a of octenyl succinic anhydride and isopropanol is added dropwise, and the dripping is controlled to be completed within 30 min. After the dripping is completed, the speed is maintained unchanged, the temperature is raised to 65° C., and the stirring reaction is continued for 6 h. After the reaction is completed, the pH value is adjusted to 5.5, and the mixture is washed with deionized water to neutrality, dried at 50° C. to constant weight, crushed, and passed through a 40-mesh sieve to obtain esterified corn starch, wherein the mass ratio of corn starch, deionized water and mixed solution a is 1:25:110, and the mass ratio of octenyl succinic anhydride and isopropanol in the mixed solution a is 2:110; Step B2, add esterified corn starch to anhydrous DMF, control the speed to 600rpm and stir for 35min until uniform, add tetrabutylammonium bromide, the epoxy compound prepared in Preparation Example 1 and the mixed solution b of anhydrous DMF while stirring, and control the dripping to be completed within 30min. After the dripping is completed, the temperature is raised to 70°C, and the reaction is stirred for 6h. After the reaction is completed, centrifuge, wash with anhydrous ethanol and deionized water three times in sequence, and dry at 55°C to constant weight to obtain modified starch, wherein the mass ratio of esterified corn starch, anhydrous DMF and mixed solution b is 2:60:15, and the mass ratio of tetrabutylammonium bromide, epoxy compound and anhydrous DMF in the mixed solution b is 0.04:0.3:20.

[0024] Preparation Example 5 Modified starch is prepared by the following steps: Step B1, corn starch and deionized water are stirred at 40° C. and the speed is controlled to be 600 rpm for 20 min until uniform, the pH value is adjusted to 9.0 with 0.7M sodium hydroxide aqueous solution, and then a mixed solution a of octenyl succinic anhydride and isopropanol is added dropwise, and the dripping is controlled to be completed within 30 min. After the dripping is completed, the speed is maintained unchanged, the temperature is raised to 70° C., and the stirring reaction is continued for 5 h. After the reaction is completed, the pH value is adjusted to 6.0, and the mixture is washed with deionized water to neutrality, dried at 55° C. to constant weight, crushed, and passed through a 50-mesh sieve to obtain esterified corn starch, wherein the mass ratio of corn starch, deionized water and mixed solution a is 2:30:110, and the mass ratio of octenyl succinic anhydride and isopropanol in the mixed solution a is 3:110; Step B2, add esterified corn starch to anhydrous DMF, control the speed to 700rpm and stir for 25min until uniform, add tetrabutylammonium bromide, the epoxy compound prepared in Preparation Example 2 and the mixed solution b of anhydrous DMF while stirring, and control the dripping to be completed within 30min. After the dripping is completed, the temperature is raised to 75°C, and the reaction is stirred for 5h. After the reaction is completed, centrifuge, wash with anhydrous ethanol and deionized water 4 times in sequence, and dry at 60°C to constant weight to obtain modified starch, wherein the mass ratio of esterified corn starch, anhydrous DMF and mixed solution b is 3:70:20, and the mass ratio of tetrabutylammonium bromide, epoxy compound and anhydrous DMF in the mixed solution b is 0.05:0.45:25.

[0025] Preparation Example 6 Modified starch is prepared by the following steps: Step B1, corn starch and deionized water are stirred at 45°C, the speed is controlled to be 700rpm for 10min until uniform, the pH value is adjusted to 9.5 with 0.8M sodium hydroxide aqueous solution, and then a mixed solution a of octenyl succinic anhydride and isopropanol is added dropwise, and the dripping is controlled to be completed within 30min. After the dripping is completed, the speed is maintained unchanged, the temperature is raised to 75°C, and the stirring reaction is continued for 4h. After the reaction is completed, the pH value is adjusted to 6.5, and the mixture is washed with deionized water to neutrality, dried at 60°C to constant weight, crushed, and passed through a 60-mesh sieve to obtain esterified corn starch, wherein the mass ratio of corn starch, deionized water and mixed solution a is 3:35:110, and the mass ratio of octenyl succinic anhydride and isopropanol in the mixed solution a is 4:110; Step B2, add esterified corn starch to anhydrous DMF, control the speed to 800rpm and stir for 15min until uniform, add tetrabutylammonium bromide, the epoxy compound prepared in Preparation Example 3 and the mixed solution b of anhydrous DMF while stirring, and control the dripping to be completed within 30min. After the dripping is completed, the temperature is raised to 80°C, and the reaction is stirred for 4h. After the reaction is completed, centrifuge, wash with anhydrous ethanol and deionized water for 5 times in sequence, and dry at 65°C to constant weight to obtain modified starch, wherein the mass ratio of esterified corn starch, anhydrous DMF and mixed solution b is 4:80:25, and the mass ratio of tetrabutylammonium bromide, epoxy compound and anhydrous DMF in the mixed solution b is 0.06:0.6:30.

[0026] Comparative Preparation Example 2 Modified starch is prepared by the following steps: Step B1, corn starch and deionized water are stirred at 35° C. and the speed is controlled to be 500 rpm for 30 min until uniform, the pH value is adjusted to 8.5 with 0.6M sodium hydroxide aqueous solution, and then a mixed solution a of octenyl succinic anhydride and isopropanol is added dropwise, and the dripping is controlled to be completed within 30 min. After the dripping is completed, the speed is maintained unchanged, the temperature is raised to 65° C., and the stirring reaction is continued for 6 h. After the reaction is completed, the pH value is adjusted to 5.5, and the mixture is washed with deionized water to neutrality, dried at 50° C. to constant weight, crushed, and passed through a 40-mesh sieve to obtain esterified corn starch, wherein the mass ratio of corn starch, deionized water and mixed solution a is 1:25:110, and the mass ratio of octenyl succinic anhydride and isopropanol in the mixed solution a is 2:110; Step B2, add esterified corn starch to anhydrous DMF, control the speed to 600rpm and stir for 35min until uniform, add tetrabutylammonium bromide, the epoxy compound prepared in Comparative Preparation Example 1 and the mixed solution b of anhydrous DMF while stirring, and control the dripping within 30min. After the dripping, heat to 70°C, stir and react for 6h. After the reaction, centrifuge, wash with anhydrous ethanol and deionized water 3 times in sequence, and dry at 55°C to constant weight to obtain modified starch, wherein the mass ratio of esterified corn starch, anhydrous DMF and mixed solution b is 2:60:15, and the mass ratio of tetrabutylammonium bromide, epoxy compound and anhydrous DMF in the mixed solution b is 0.04:0.3:20.

[0027] Comparative Preparation Example 3 Modified starch is prepared by the following steps: Step B1, corn starch and deionized water are stirred at 35° C. and the speed is controlled to be 500 rpm for 30 min until uniform, the pH value is adjusted to 8.5 with 0.6M sodium hydroxide aqueous solution, and then a mixed solution a of n-octyl succinic anhydride and isopropanol is added dropwise, and the dripping is controlled to be completed within 30 min. After the dripping is completed, the speed is maintained unchanged, the temperature is raised to 65° C., and the stirring reaction is continued for 6 h. After the reaction is completed, the pH value is adjusted to 5.5, and the mixture is washed with deionized water to neutrality, dried at 50° C. to constant weight, crushed, and passed through a 40-mesh sieve to obtain esterified corn starch, wherein the mass ratio of corn starch, deionized water and mixed solution a is 1:25:110, and the mass ratio of n-octyl succinic anhydride and isopropanol in the mixed solution a is 2:110; Step B2, add esterified corn starch to anhydrous DMF, control the speed to 600rpm and stir for 35min until uniform, add tetrabutylammonium bromide, the epoxy compound prepared in Preparation Example 1 and the mixed solution b of anhydrous DMF while stirring, and control the dripping to be completed within 30min. After the dripping is completed, the temperature is raised to 70°C, and the reaction is stirred for 6h. After the reaction is completed, centrifuge, wash with anhydrous ethanol and deionized water three times in sequence, and dry at 55°C to constant weight to obtain modified starch, wherein the mass ratio of esterified corn starch, anhydrous DMF and mixed solution b is 2:60:15, and the mass ratio of tetrabutylammonium bromide, epoxy compound and anhydrous DMF in the mixed solution b is 0.04:0.3:20.

[0028] Preparation Examples 7-9 and Comparative Preparation Examples 4-6 provide methods for preparing functionalized adhesives.

[0029] Preparation Example 7 The functionalized adhesive is prepared by the following steps: Step A1, prepare the following raw materials in parts by weight: 16 parts of corn starch, 12 parts of deionized water, 18 parts of sodium tripolyphosphate, 22 parts of modified starch prepared in Preparation Example 4, 6 parts of pentaerythritol allyl ether and 0.3 parts of initiator solution, wherein the initiator solution is an ammonium persulfate solution with a mass fraction of 10%; Step A2, gelatinization: add corn starch and sodium tripolyphosphate to 1 / 3 weight part of deionized water, control the speed to 600 rpm while stirring and heating to 65° C., continue stirring for 20 minutes to obtain gelatinized corn starch; Step A3, free radical polymerization: add the modified starch to the remaining weight of deionized water, control the speed to 700 rpm and stir for 30 minutes until uniform, add the gelatinized corn starch prepared in step S2 while stirring, continue stirring for 3 hours, then add pentaerythritol allyl ether and initiator solution, raise the temperature to 76°C, continue stirring for 8 hours, and obtain a functionalized adhesive.

[0030] Preparation Example 8 The functionalized adhesive is prepared by the following steps: Step A1, prepare the following raw materials in parts by weight: 24 parts of corn starch, 18 parts of deionized water, 27 parts of sodium tripolyphosphate, 31 parts of modified starch prepared in Preparation Example 5, 8 parts of pentaerythritol allyl ether and 0.4 parts of initiator solution, wherein the initiator solution is an ammonium persulfate solution with a mass fraction of 10%; Step A2, gelatinization: add corn starch and sodium tripolyphosphate to 1 / 3 parts by weight of deionized water, control the speed to 700 rpm while stirring and raise the temperature to 70° C., continue stirring for 15 minutes to obtain gelatinized corn starch; Step A3, free radical polymerization: add the modified starch to the remaining weight parts of deionized water, control the speed to stir evenly, add the gelatinized corn starch prepared in step S2 while stirring, continue stirring for 2.5 hours, then add pentaerythritol allyl ether and initiator solution, raise the temperature to 78°C, continue stirring for 7 hours, and obtain a functionalized adhesive.

[0031] Preparation Example 9 The functionalized adhesive is prepared by the following steps: Step A1, prepare the following raw materials in parts by weight: 32 parts of corn starch, 24 parts of deionized water, 36 parts of sodium tripolyphosphate, 40 parts of modified starch prepared in Preparation Example 6, 10 parts of pentaerythritol allyl ether and 0.5 parts of initiator solution, wherein the initiator solution is an ammonium persulfate solution with a mass fraction of 10%; Step A2, gelatinization: add corn starch and sodium tripolyphosphate into 1 / 3 parts by weight of deionized water, control the speed to 800 rpm while stirring and heating to 75° C., continue stirring for 10 minutes to obtain gelatinized corn starch; Step A3, free radical polymerization: add the modified starch to the remaining weight of deionized water, stir evenly, add the gelatinized corn starch prepared in step S2 while stirring, continue stirring for 3 hours, then add pentaerythritol allyl ether and initiator solution, heat to 80°C, continue stirring for 6 hours to obtain a functionalized adhesive.

[0032] Comparative Preparation Example 4 The functionalized adhesive is prepared by the following steps: Step A1, prepare the following raw materials in parts by weight: 16 parts of corn starch, 12 parts of deionized water, 18 parts of sodium tripolyphosphate, 22 parts of modified starch prepared in Comparative Preparation Example 2, 6 parts of pentaerythritol allyl ether and 0.3 parts of initiator solution, wherein the initiator solution is an ammonium persulfate solution with a mass fraction of 10%; Step A2, gelatinization: add corn starch and sodium tripolyphosphate to 1 / 3 weight part of deionized water, control the speed to 600 rpm while stirring and heating to 65° C., continue stirring for 20 minutes to obtain gelatinized corn starch; Step A3, free radical polymerization: add the modified starch to the remaining weight of deionized water, control the speed to 700 rpm and stir for 30 minutes until uniform, add the gelatinized corn starch prepared in step S2 while stirring, continue stirring for 3 hours, then add pentaerythritol allyl ether and initiator solution, raise the temperature to 76°C, continue stirring for 8 hours, and obtain a functionalized adhesive.

[0033] Comparative Preparation Example 5 The functionalized adhesive is prepared by the following steps: Step A1, prepare the following raw materials in parts by weight: 16 parts of corn starch, 12 parts of deionized water, 18 parts of sodium tripolyphosphate, 22 parts of modified starch prepared in Comparative Preparation Example 3, 6 parts of pentaerythritol allyl ether and 0.3 parts of initiator solution, wherein the initiator solution is an ammonium persulfate solution with a mass fraction of 10%; Step A2, gelatinization: add corn starch and sodium tripolyphosphate to 1 / 3 weight part of deionized water, control the speed to 600 rpm while stirring and heating to 65° C., continue stirring for 20 minutes to obtain gelatinized corn starch; Step A3, free radical polymerization: add the modified starch to the remaining weight of deionized water, control the speed to 700 rpm and stir for 30 minutes until uniform, add the gelatinized corn starch prepared in step S2 while stirring, continue stirring for 3 hours, then add pentaerythritol allyl ether and initiator solution, raise the temperature to 76°C, continue stirring for 8 hours, and obtain a functionalized adhesive.

[0034] Comparative Preparation Example 6 The functionalized adhesive is prepared by the following steps: Step A1, prepare the following raw materials in parts by weight: 16 parts of corn starch, 12 parts of deionized water, 18 parts of sodium tripolyphosphate, 22 parts of modified starch prepared in Preparation Example 4, 6 parts of pentaerythritol glycidyl ether and 0.3 parts of initiator solution, wherein the initiator solution is an ammonium persulfate solution with a mass fraction of 10%; Step A2, gelatinization: add corn starch and sodium tripolyphosphate to 1 / 3 weight part of deionized water, control the speed to 600 rpm while stirring and heating to 65° C., continue stirring for 20 minutes to obtain gelatinized corn starch; Step A3, free radical polymerization: add the modified starch to the remaining weight of deionized water, control the speed to 700 rpm and stir for 30 minutes until uniform, add the gelatinized corn starch prepared in step S2 while stirring, continue stirring for 3 hours, then add pentaerythritol glycidyl ether and initiator solution, raise the temperature to 76°C, continue stirring for 8 hours, and obtain a functionalized adhesive.

[0035] Preparation Examples 10-12 provide methods for preparing blue charcoal coke powder.

[0036] Preparation Example 10 Blue charcoal coke powder is prepared by the following steps: The semi-coke was crushed and sieved into two particle sizes of 0-1mm and 1-3mm, and stirred at a speed of 400 rpm for 30 minutes at a ratio of 4:1 until uniform, to obtain semi-coke coke powder.

[0037] Preparation Example 11 Blue charcoal coke powder is prepared by the following steps: The semi-coke was crushed and sieved into two particle sizes of 0-1mm and 1-3mm, and stirred at a speed of 500rpm for 20min at a ratio of 4.5:1 until uniform, to obtain semi-coke coke powder.

[0038] Preparation Example 12 Blue charcoal coke powder is prepared by the following steps: The semi-coke was crushed and sieved into two particle sizes of 0-1mm and 1-3mm, and stirred at a speed of 600 rpm for 10 minutes at a ratio of 5:1 until uniform, to obtain semi-coke coke powder.

[0039] Examples 1-6 and Comparative Examples 1-6 provide a clean and environmentally friendly carbon.

[0040] Example 1 This embodiment provides a clean and environmentally friendly carbon, which is prepared by the following steps: Step S1, preparing the following raw materials in parts by weight: 100 parts of blue charcoal powder prepared in Preparation Example 10, 15 parts of deionized water, and 9 parts of the functionalized binder prepared in Preparation Example 7; Step S2, preparing clean and environmentally friendly carbon: stirring the blue carbon powder and the functionalized binder at a rotation speed of 500 rpm for 20 min until uniform, adding deionized water, and then pressing them into spheres with a diameter of 3 cm at 6 MPa, and drying them at 90° C. to constant weight to obtain clean and environmentally friendly carbon.

[0041] Example 2 This embodiment provides a clean and environmentally friendly carbon, which is prepared by the following steps: Step S1, prepare the following raw materials in parts by weight: 105 parts of blue charcoal powder prepared in Preparation Example 11, 16 parts of deionized water, and 10.5 parts of the functionalized binder prepared in Preparation Example 8; Step S2, stirring the blue charcoal powder and the functionalized binder at a rotation speed of 600 rpm for 15 minutes until uniform, adding deionized water, and then pressing them into spheres with a diameter of 6 cm at 7 MPa, and drying them at 95° C. to constant weight to obtain clean and environmentally friendly carbon.

[0042] Example 3 This embodiment provides a clean and environmentally friendly carbon, which is prepared by the following steps: Step S1, preparing the following raw materials in parts by weight: 110 parts of blue charcoal powder prepared in Preparation Example 12, 17 parts of deionized water, and 12 parts of the functionalized binder prepared in Preparation Example 9; Step S2, preparing clean and environmentally friendly carbon: stirring the blue carbon powder and the functionalized binder at a rotation speed of 700 rpm for 10 min until uniform, adding deionized water, and then pressing them into spheres with a diameter of 6 cm at 8 MPa, and drying them at 100° C. to constant weight to obtain clean and environmentally friendly carbon.

[0043] Example 4 This embodiment provides a clean and environmentally friendly carbon, which is prepared by the following steps: Step S1, preparing the following raw materials in parts by weight: 100 parts of blue charcoal powder prepared in Preparation Example 10, 15 parts of deionized water, and 9 parts of the functionalized binder prepared in Preparation Example 7; Step S2, stirring the blue charcoal powder and the functionalized binder at a rotation speed of 500 rpm for 20 minutes until uniform, adding deionized water, and then pressing them into cylindrical strips with a diameter of 3 cm and a height of 3 cm at 6 MPa, and drying them at 90°C to constant weight to obtain clean and environmentally friendly carbon.

[0044] Example 5 This embodiment provides a clean and environmentally friendly carbon, which is prepared by the following steps: Step S1, prepare the following raw materials in parts by weight: 105 parts of blue charcoal powder prepared in Preparation Example 11, 16 parts of deionized water, and 10.5 parts of the functionalized binder prepared in Preparation Example 8; Step S2, stirring the blue charcoal powder and the functionalized binder at a rotation speed of 600 rpm for 15 minutes until uniform, adding deionized water, and then pressing them into cylindrical strips with a diameter of 6 cm and a height of 6 cm at 7 MPa, and drying them at 95°C to constant weight to obtain clean and environmentally friendly carbon.

[0045] Example 6 This embodiment provides a clean and environmentally friendly carbon, which is prepared by the following steps: Step S1, preparing the following raw materials in parts by weight: 110 parts of blue charcoal powder prepared in Preparation Example 12, 17 parts of deionized water, and 12 parts of the functionalized binder prepared in Preparation Example 9; Step S2, preparing clean and environmentally friendly carbon: stirring the blue carbon powder and the functionalized binder at a rotation speed of 800 rpm for 10 min until uniform, adding deionized water, and then pressing them into cylindrical strips with a diameter of 8 cm and a height of 8 cm at 8 MPa, and drying them at 100°C to constant weight to obtain clean and environmentally friendly carbon.

[0046] Comparative Example 1 This embodiment provides a clean and environmentally friendly carbon, which is prepared by the following steps: Step S1, preparing the following raw materials in parts by weight: 100 parts of blue charcoal powder prepared in Preparation Example 10, 15 parts of deionized water, and 9 parts of the functionalized binder prepared in Comparative Preparation Example 4; Step S2, preparing clean and environmentally friendly carbon: stirring the blue charcoal powder and the functionalized binder at a rotation speed of 500 rpm for 20 minutes until uniform, adding deionized water, and then pressing them into spheres with a diameter of 3 cm at 6 MPa to obtain clean and environmentally friendly carbon.

[0047] Comparative Example 2 This embodiment provides a clean and environmentally friendly carbon, which is prepared by the following steps: Step S1, preparing the following raw materials in parts by weight: 100 parts of blue charcoal powder prepared in Preparation Example 10, 15 parts of deionized water, and 9 parts of the functionalized binder prepared in Comparative Preparation Example 5; Step S2, preparing clean and environmentally friendly carbon: the blue charcoal powder and the functionalized binder prepared in Preparation Example 10 are stirred at a rotation speed of 500 rpm for 20 minutes until uniform, and deionized water is added, and then pressed into a sphere with a diameter of 3 cm at 6 MPa, and dried at 90°C to constant weight to obtain clean and environmentally friendly carbon.

[0048] Comparative Example 3 This embodiment provides a clean and environmentally friendly carbon, which is prepared by the following steps: Step S1, preparing the following raw materials in parts by weight: 100 parts of blue charcoal powder prepared in Preparation Example 10, 15 parts of deionized water, and 9 parts of the functionalized binder prepared in Comparative Preparation Example 6; Step S2, preparing clean and environmentally friendly carbon: stirring the blue charcoal powder and the functionalized binder at a rotation speed of 500 rpm for 20 minutes until uniform, adding deionized water, and then pressing them into spheres with a diameter of 3 cm at 6 MPa to obtain clean and environmentally friendly carbon.

[0049] Performance Testing The combustion performance of the clean and environmentally friendly carbon prepared in Examples 1-6 and Comparative Examples 1-3 provided in this application was tested according to the national standard GB / T 213-2008; the parameters such as moisture content and ash content of the environmentally friendly carbon provided in Examples 1-6 and Comparative Examples 1-3 provided in the application were tested and analyzed according to the national standard GB / T212-2008. All test results are shown in Table 2 below. Table 2 Test data of anti-crushing and combustion performance of clean and environmentally friendly carbon

[0050] It can be seen from the experimental data in Table 2 that the clean and environmentally friendly carbon prepared according to the method provided in this application has higher crushing strength and cold pressing strength, and at the same time has lower ash and sulfur content, and meets the standards of clean gasification carbon.

[0051] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. Clean and environmentally friendly carbon, characterized in that: Prepared by the following steps: Step S1, preparing the following raw materials in parts by weight: 100-110 parts of blue charcoal coke powder, 15-17 parts of deionized water and 9-12 parts of functionalized binder; Step S2, preparing clean and environmentally friendly carbon: mixing the blue carbon powder and the functionalized binder evenly, adding deionized water, and then pressing into a 3-8 cm long strip or ball shape, and drying to obtain clean and environmentally friendly carbon; The functionalized adhesive is prepared by gelatinizing corn starch to obtain gelatinized corn starch, and then further reacting the corn starch with modified starch and pentaerythritol allyl ether through free radical polymerization. The modified starch is prepared by a ring-opening esterification reaction between corn starch and octenyl succinic anhydride to obtain esterified corn starch, which is then further subjected to a ring-opening reaction with an epoxy compound. The epoxy compound is firstly prepared by a nucleophilic substitution reaction between calcium gluconate and epichlorohydrin.

2. The clean and environmentally friendly carbon according to claim 1, characterized in that: The functionalized binder is prepared by the following steps: Step A1, prepare the following raw materials in parts by weight: 16-32 parts of corn starch, 12-24 parts of deionized water, 18-36 parts of sodium tripolyphosphate, 22-40 parts of modified starch, 6-10 parts of pentaerythritol allyl ether and 0.3-0.5 parts of initiator solution; Step A2, gelatinization: add corn starch and sodium tripolyphosphate to 1 / 3 weight part of deionized water, raise the temperature to 65-75° C. while stirring, and continue stirring for 10-20 minutes to obtain gelatinized corn starch; Step A3, free radical polymerization: add the modified starch to the remaining weight of deionized water, stir evenly, add the gelatinized corn starch prepared in step S2 while stirring, continue stirring for 2-3 hours, then add pentaerythritol allyl ether and initiator solution, heat to 76-80°C, continue stirring for 6-8 hours to obtain a functionalized adhesive.

3. The clean and environmentally friendly carbon according to claim 1, characterized in that: The modified starch is prepared by the following steps: Step B1, mix corn starch and deionized water at 35-45° C., adjust the pH value to 8.5-9.5, then drip a mixture of octenyl succinic anhydride and isopropanol, and control the dripping to be completed within 30 minutes. After the dripping is completed, heat to 65-75° C., continue stirring and reacting for 4-6 hours. After the reaction is completed, adjust the pH value to 5.5-6.5, wash to neutral, dry, crush, and pass through a 40-60 mesh sieve to obtain esterified corn starch; Step B2, add esterified corn starch to anhydrous DMF, stir evenly, add tetrabutylammonium bromide, epoxy compound and anhydrous DMF mixture b dropwise while stirring, and control the dropping to be completed within 30 minutes. After the dropping is completed, heat to 70-80°C, stir and react for 4-6 hours. After the reaction is completed, centrifuge, wash and dry to obtain modified starch.

4. The clean and environmentally friendly carbon according to claim 3, characterized in that: In the step B1, the mass ratio of corn starch, deionized water and mixed solution a is 1-3:25-35:110, and in the mixed solution a, the mass ratio of octenyl succinic anhydride and isopropanol is 2-4:

110.

5. The clean and environmentally friendly carbon according to claim 3, characterized in that: In the step B2, the mass ratio of esterified corn starch, anhydrous DMF and mixed solution b is 2-4:60-80:15-25, and in the mixed solution b, the mass ratio of tetrabutylammonium bromide, epoxy compound and anhydrous DMF is 0.04-0.06:0.3-0.6:20-30.

6. The clean and environmentally friendly carbon according to claim 3, characterized in that: The epoxy compound is prepared by the following steps: Add calcium gluconate and triethylamine to anhydrous DMF, mix well under ice-water bath, then add dropwise a mixture c of epichlorohydrin and anhydrous DMF, control the dropping to be completed within 15 min, raise the temperature to 55-65 ° C, stir and react for 8-10 h. After the reaction is completed, filter, and rotary evaporate the filtrate. Dissolve the rotary evaporated product in acetone, filter, and rotary evaporate the filtrate to constant weight to obtain an epoxy compound.

7. The clean and environmentally friendly carbon according to claim 6, characterized in that: The mass ratio of calcium gluconate, triethylamine, anhydrous DMF, mixed solution c and acetone is 2-4: 0.1-0.3: 40-50: 15-25: 30-40. In the mixed solution c, the mass ratio of epichlorohydrin and anhydrous DMF is 0.4-0.8: 12-16.

8. The clean and environmentally friendly carbon according to claim 6, characterized in that: The initiator solution is an ammonium persulfate solution with a mass fraction of 10%.